Pengaruh Pemberian Buah Pisang Ambon Terhadap Peningkatan Kadar Hemoglobin pada Ibu Hamil Trimester III dengan Anemia: Literature Review - Pramesti, Meisy Maulani; Sukyati, Ira (Maternal & Neonatal Health Journal, 2025)
Iron deficiency is the most common cause of anaemia in pregnant women during the third trimester. The risk of pregnant women experiencing anaemia is almost three times higher than in the first and second trimesters because the fetus collects its iron reserves in the first month after birth. to determine the effect of banana ambon fruit on increasing haemoglobin levels in third trimester pregnant women with anaemia. using the literature review method with secondary data from previous studies, the search was adjusted to the keywords and inclusion criteria and using the Google Schoolar database. Based on 7 articles reviewed, giving 2 ambon bananas every day in the morning and evening routinely as one of the non-pharmacological therapies to increase Hb levels in third trimester pregnant women because ambon bananas contain vitamin C and iron. It can be concluded that there is an effect of giving ambon banana fruit as an effort to increase haemoglobin levels in third trimester pregnant women with anaemia.